COMMUNICATION TECHNIQUES FOR COMPUTER LITERACY IN INDIA: A CASE STUDY ON AKSHAYA - M. Neelamalar and Laya Kuttan (Mass Communicator, 2008)
Computers and communication developments using computers have become the norm of the present day world. Everyday life is getting more and more digitized. Computers have become a condition for the development of any kind. In spite of all this. large slice of India's population remains computer illiterates. This calls for an urgent transformation of the common man into computer literate so that all the citizens will be part of the revolution that is happening in the country. This study deals with the communication techniques involved in spreading computer literacy towards the commonman. The study is being done about a successful project of the Government of Kerala named 'Akshaya'. Through this study various communication strategies involved in 'Akshaya' have been found along with the effectiveness of the project through a survey.